P09.11 TLR3 suppresses colorectal carcinogenesis, presumably through up-regulation of T-cell attracting CXC chemokines. (1st October 2020) - Sichler, A; Frey, M; Johannes, W; Janssen, K
Abstract : Background: Toll-like-receptors (TLRs) are main components of the innate immune system which recognize endogenous or pathogen-associated molecular 'danger patterns'. Previous findings from us and others highlighted a role of TLRs in the formation of tumors. However, TLRs may have differing roles in immune and cancer cells, and the underlying mechanisms are still unclear. TLR downstream signaling is mediated by two adapter proteins; MyD88 (myeloid differentiation primary response gene 88) and TRIF (TIR-domain-containing adapter-inducing interferon-β). The MyD88-mediated signaling pathway is activated by all TLRs, except TLR3. We could show previously that it leads to the initiation of oncogenic, proliferative and pro-inflammatory responses in colorectal cancer. The endosomal receptor TLR3, in contrast, solely depends on TRIF. It recognizes viral, microbial and endogenous dsRNA leading to production of type-I interferon and chemokines, and induces apoptosis. The role of TRIF dependent TLR3 signaling in colorectal cancer is still disputed. Within this study, we show tumor-suppressive TLR3 functions prevailing over oncogenic effects in colorectal cancer. Materials and Methods: TLR3-deficient colon cancer cell lines were engineered by CRISPR-Cas9. Genetically modified mouse models were generated, based on a 'switch-on mutagenesis' approach, with global inactivation of Tlr3 or TRIF (Ticam1), allowing tissue specific re-expression based on Cre recombination. The mice were interbred with the Apc 1638N mouse model for digestive cancer. Furthermore, clinical significance of TLR3 expression levels was assessed in human colorectal cancer tissue samples from our clinic (n=81) and from TCGA datasets. A putative correlation between intratumoral TLR3 expression and T-cell infiltration is currently analyzed. Results: Global deficiency of murine Tlr3, or TRIF, induced significantly increased digestive tumor formation, associated with increased morbidity indicating a tumor suppressive role. Coherently, TLR3 expression is highly significantly decreased in human colorectal cancer compared to normal mucosa, significantly correlated with poor survival. TLR3 deficient cell lines show reduced migration and slightly declined proliferation suggesting an oncogenic role on the cell-autonomous level. Nevertheless, gene expression analysis revealed that the dsRNA induced expression of T-cell attracting cytokines CXCL10 and CXCL11 in colon cancer cell lines is exclusively dependent on TLR3. These chemokines were shown to favor a TH1-type antitumoral response. Conclusions: TLR3 favors tumor suppression in vivo, presumably resulting from non-cell-autonomous factors such as the production of CXCL10 and 11 and resulting T-cell infiltration. This may outweigh the putative cell-autonomous oncogenic functions of TLR3 deficiency. Disclosure Information: A. Sichler: None. M. Frey: None. W. Johannes: None. K. Janssen: None.